2007
DOI: 10.1021/ja076235t
|View full text |Cite
|
Sign up to set email alerts
|

Side Chain Disorder and Phase Transitions in Alkyl-Substituted, Conjugated Oligomers. Relation to Side-Chain Melting in P3ATs

Abstract: Certain 4,4'-alkyl substituted 2,2'-bithiazole and bithiazole-thiophene oligomers display an endothermic transition in their DSC trace below their respective melting points. Variable-temperature FTIR, MAS-1H NMR, UV-vis spectra, and XRD all indicate that the thermal transition is due to a crystal-crystal phase transition that we have labeled alpha --> beta. FTIR shows a stepwise increase in the concentration of gauche defects at the alpha --> beta transition temperature, but MAS NMR spectra show little increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 93 publications
2
24
0
Order By: Relevance
“…To further study the polymer conformation changes, FT-IR spectroscopy was used to discern the structural information from vibrational resonances of different functional groups. A polymer film was cast from the polymer solution onto a KBr disk, which was then immersed in the solvent vapor atmosphere and dried before FT-IR measurements [28,31]. Similar patterns with slight differences in conformations were observed in the spectra of PP8P films cast from the different solvents, as shown in Fig.…”
Section: Spectroscopic Analyses Of Pp8p From Single Solventssupporting
confidence: 56%
See 1 more Smart Citation
“…To further study the polymer conformation changes, FT-IR spectroscopy was used to discern the structural information from vibrational resonances of different functional groups. A polymer film was cast from the polymer solution onto a KBr disk, which was then immersed in the solvent vapor atmosphere and dried before FT-IR measurements [28,31]. Similar patterns with slight differences in conformations were observed in the spectra of PP8P films cast from the different solvents, as shown in Fig.…”
Section: Spectroscopic Analyses Of Pp8p From Single Solventssupporting
confidence: 56%
“…In order to get more information on the solvent-induced phase separation, the FT-IR spectroscopy experiments [28,31,33] on the polymeric films deposited on KBr disks were also performed. The spectra of PP8P from the different mixed solutions were presented in Fig.…”
Section: Phase Separations In Mixed Solventsmentioning
confidence: 99%
“…The results presented can influence many aspects of our understanding of thiophene‐based materials. In particular, the existence of accessible conformations other than the linear all‐anti one can affect estimates of the intramolecular and intermolecular components of the internal energy in crystals, side chain disorder and side chain melting, dynamical behavior and charge transport phenomena, thermal behavior and phase transitions, as well as the choice of the most appropriate molecular modeling approach (including force field parameterization) for substituted aromatics. Work is in progress in our group to explore some of these issues through structural and modeling studies of 3‐alkylthiophene oligomers and polymers.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, copolymers and co‐oligomers of thiophene and thiazole are considered to have an intramolecular charge‐transferred (CT) electronic state, and such copolymers and co‐oligomers have attracted recent interest 4–13. For example, the synthesis of the type of copolymers and co‐oligomers shown below via organometallic routes has been reported 4–7. The electrochemical synthesis of analogous copolymers has also been reported 14, 15…”
Section: Introductionmentioning
confidence: 99%
“…Copolymers and co‐oligomers behave as active materials in field‐effect transistors (FETs) 5–7. Recently, it has been reported that copolymers of bithiophene and dialkyl‐bithiazole show a strong tendency to self‐assemble and to form a well‐packed solid structure 9–13.…”
Section: Introductionmentioning
confidence: 99%